1992
DOI: 10.1136/bjo.76.6.349
|View full text |Cite
|
Sign up to set email alerts
|

Management of traumatic optic neuropathy--a study of 23 patients.

Abstract: Twenty three patients with traumatic optic neuropathy were managed by medical and surgical treatment as follows. High dose intravenous steroids were initiated in all patients. If visions did not improve significantly after 24 to 48 hours decompression of an optic nerve sheath haematoma by medial orbitotomy and neurosurgical decompression of the optic canal were considered based on computed tomographic scan findings. Nine of 16 patients who received steroids only showed significant improvement. One of three sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This is similar to Levin's study [5], in which they concluded that initial visual acuity after trauma is a powerful prognostic factor in final visual acuity. This relation was also detected in other studies [9,11]. In our study, visual recovery in the first 48 h was a prognostic factor for final visual acuity.…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to Levin's study [5], in which they concluded that initial visual acuity after trauma is a powerful prognostic factor in final visual acuity. This relation was also detected in other studies [9,11]. In our study, visual recovery in the first 48 h was a prognostic factor for final visual acuity.…”
Section: Discussionsupporting
confidence: 87%
“…1,4,5 Various options include high-dose [6][7][8] or low-dose 9 corticosteroids, immediate decompression of the canalicular portion of the optic nerve, 10 decompression of the canalicular optic nerve after a course of systemic corticosteroids, 11,12 observation, and optic nerve sheath fenestration in cases of anterior TON. 3 Unfortunately, findings in published reports have been inadequate to determine which, if any, of these treatments improves visual outcome after TON, mainly because of retrospective design, small numbers of matched cases, treatment bias, and unmasked outcomes.…”
mentioning
confidence: 99%
“…Steroid therapy in TON has been examined in multiple case series, mostly nonrandomized, unblended and without controls. [ 4 5 ] The doses used in these trials can be categorized as follows: Moderate dose (60–100 mg of oral prednisolone), high dose (1 g of intravenous [IV] methylprednisolone/day), or megadose (30 mg/kg loading dose of IV methylprednisone, followed by 5.4 mg/kg/h for 24 h). The expected role of steroids has been in reducing inflammation and edema in the closed confines of the optic canal thereby preventing secondary compressive damage and providing neuroprotection by virtue of preventing free radical induced lipid peroxidation.…”
Section: Treatmentmentioning
confidence: 99%